2016
DOI: 10.1007/s00709-016-0947-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and intercontinental tests show synchronism between the local gravimetric tide and the ultra-weak photon emission in seedlings of different plant species

Abstract: In order to corroborate the hypothesis that variations in the rate of spontaneous ultra-weak photon emission (UPE) from germinating seedlings are related to local variations of the lunisolar tidal force, a series of simultaneous tests was performed using the time courses of UPE collected from three plant species-corn, wheat and sunflower-and also from wheat samples whose grains were transported between continents, from Brazil to The Netherlands and vice versa. All tests which were run in parallel showed coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Long term variations in UPE measured from multiple seedlings have been noted previously in tests [17 , 18] . For single seedlings, one possible cause of UPE variation could be the different position or orientation of the growing seedling relative to the PMT active cathode.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Long term variations in UPE measured from multiple seedlings have been noted previously in tests [17 , 18] . For single seedlings, one possible cause of UPE variation could be the different position or orientation of the growing seedling relative to the PMT active cathode.…”
Section: Resultssupporting
confidence: 70%
“…Under acute stress, when a chemical stressor is applied after the first days of germination, the response is the opposite, with the more damaged, less developed sprouts presenting higher photon-counts, just after the stress, than the control samples, and the burst lasting for few hours (6–12 h) [16] . Our group also presented evidence that non-stressed samples presented daily and monthly oscillations behaving similar to the local gravimetric tide profile, with coincident pattern inflections and similar periodic components for different species [17 , 18] .…”
Section: Introductionsupporting
confidence: 58%
“…It was also shown that the UPE profiles for seedlings of different species measured in parallel, e.g. wheat-corn and corn-sunflower (Helianthus annuus), present turning points consistently coincident with those of the local gravity tide (Gallep et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…A further contribution in this field appeared recently, in collaboration with colleagues at the University of Leiden, Netherlands (Gallep et al, 2017). UPEs were measured from wheat seedlings taken from a stock transported overseas from Brazil to the Netherlands (direct São Paulo to Amsterdam) and back, in July 2014, taken in parallel with those from local stocks.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Peter's interests turned towards the moon and the influence that this satellite may have on biological phenomena on Earth [99]. That conference presentation was followed up by many papers investigating the influence of the moon on such plant phenomena as leaf movements [99][100][101], stem elongation [102], fluctuations in diameters of tree stems [103], root growth [104][105][106], emissions of biophotons by seedlings [107][108][109][110], and chlorophyll fluorescence [111]. Not constrained by gravity, Peter was also developing ideas about extraterrestrial influences and plant bioelectricity [112].…”
Section: Extra-terrestrial Influences On Plant-lifementioning
confidence: 99%